1992
DOI: 10.1088/0953-8984/4/2/027
|View full text |Cite
|
Sign up to set email alerts
|

Further study of the Mn2+EPR centre in ferro- and para-elastic BiVO4:spin Hamiltonian parameters and temperature dependence

Abstract: The electron paramagnetic resonance (EPR) of an Mn2+ (S=5/2) impurity in the ferroelastic and para-elastic phase of BiVO4 crystals with a single domain, grown by the Czochralski method, has been investigated using an X-band spectrometer. The rotation patterns of the resonance fields measured on the crystallographic planes are analysed: g=1.9940+or-0.0009, D/h=2.443+or-0.002, E/h=0.4912+or-0.0009, F/h=0.094+or-0.002, B42/h=0.0, Ax/h=0.27+or-0.02, Ay/h=0.25+or-0.02, and Az/h=0.33+or-0.02 GHz at room temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
1
27
1
Order By: Relevance
“…Recently, a number of experiments, e.g. X-ray and neutron diffraction [5], Raman scattering [6][7][8], NMR [9][10][11][12], and EPR [13][14][15][16] have been carried out to investigate structural changes, phase transitions, and optical properties of BiVO4. EPR is a powerful technique in studies of local site symmetry around paramagnetic impurities in crystals.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, a number of experiments, e.g. X-ray and neutron diffraction [5], Raman scattering [6][7][8], NMR [9][10][11][12], and EPR [13][14][15][16] have been carried out to investigate structural changes, phase transitions, and optical properties of BiVO4. EPR is a powerful technique in studies of local site symmetry around paramagnetic impurities in crystals.…”
Section: Introductionmentioning
confidence: 99%
“…EPR is a powerful technique in studies of local site symmetry around paramagnetic impurities in crystals. EPR studies of Gd3+, Er3+, and Mn2+ in BiVO4 single crystals were reported [13][14][15][16]. The site symmetry of Gd 3 + centre in BiVO4 single crystal was determined [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations